Addressing Offshore Oil Rig Development by Companies in Areas Pending Maritime Boundary Delimitation - Limy, Alvin (Center for Law and Responsible Business Studies, 2025)
Due to the depletion of onshore oil and gas resources, there has been a growing effort to explore and extract oil and gas from offshore wells. This decline, in turn, catalyses the increase in number of offshore oil rigs worldwide. Such offshore exploration, however, carries inherent, present and real risk of catastrophic spills. An offshore oil rig, regardless of how meticulously it is constructed or operated, remains susceptible to disasters caused by human error, equipment and control failure, weak operating systems and procedures, hazardous materials as well as environmental phenomena. It is inevitable that every offshore hydrocarbon drilling operation carries the inherent risk of causing large-scale and far-reaching environmental pollution. Notwithstanding the growing number of offshore oil rigs worldwide, there is yet an international legal regime that establishes corporate liability for pollution resulting from offshore oil rigs. The current international legal regime which addresses corporate liability are confined to vessel-source oil pollution. The absence of any internationally agreed framework to properly regulate offshore hydrocarbon drilling creates substantial legal and environmental uncertainties, particularly in areas pending maritime boundary delimitation. This article will be addressing the legal status of offshore oil rigs whether it is fixed or mobile and what is the rights and obligations of countries in a pending delimitation over maritime boundary as well as the legal implication of oil and gas exploitation in disputed maritime area, including the corporate liability related to the offshore oil activities where the maritime area boundary is pending. The outcome of this article is to determine how effective is the current Law of the Sea in addressing such issues. This article finds that operation of offshore oil rigs in area pending maritime delimitation will cause difficulties to hold the oil rigs operator or companies liable for pollution caused by its activities. In particular, in areas pending maritime boundary, no state has jurisdiction over the exploration area. Most importantly, no international legal regime exists to hold companies or offshore oil operators liable in the event of pollution, let alone in areas pending maritime delimitation.